The holiday swap - Knox, Maggie (G.P. Putnam's Sons, 2021)
"A feel-good, holiday-themed romantic comedy about identical twins who switch lives in the days leading up to Christmas--perfect for fans of Christina Lauren's In a Holidaze and Josie Silver's One Day in December"--